The following summation of series equals . Compute .
Note :
Please provide the solution if you can answer it. Also, you may use Wolfram Alpha , but will you do that??? It's up to you. (>‿◠)✌
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Let us consider the sum:
1 + x + x 2 + x 3 + x 4 + . . . uptill infinite terms where ∣ x ∣ < 1
By the formula for the sum of an infinite Geometric Progression the above sum can be written as:
n = 0 ∑ ∞ x n = 1 − x 1
Now differentiating w.r.t. x we get:
n = 0 ∑ ∞ n x n − 1 = ( 1 − x ) 2 1
Multiplying both sides by x :
n = 0 ∑ ∞ n x n = ( 1 − x ) 2 x
Now again differentiating w.r.t. x :
n = 0 ∑ ∞ n 2 x n − 1 = ( 1 − x ) 3 1 + x
Now repeating the above process once more we get:
n = 0 ∑ ∞ n 3 x n − 1 = ( 1 − x ) 4 ( 1 − x ) ( 1 + 2 x ) + 3 ( x + x 2 )
Now substitute x = 3 1 to obtain:
n = 0 ∑ ∞ 3 n − 1 n 3 = 8 9 9
Thus the required answer is 3 1 n = 0 ∑ ∞ 3 n − 1 n 3 = 8 3 3